Procedure for collecting gastric contents in giant Amazon turtles Podocnemis expansa (Schweigger, 1812) (Testudines, Podocnemididae) - Alves Júnior, José R. F. [UNESP]; de Sousa, Eliane [UNESP]; Lustosa, Ana P. G.; Magajevski, Fernanda S. [UNESP]; Girio, Raul J. S. [UNESP]; Werther, Karin [UNESP] (My University, 2011)
The genus Podocnemis, of the family Podocnemididae, is represented in South America by six species: P. expansa, P. erytrocephala, P. vogli, P. lewyana, P. unifilis and P. sextuberculata (4, 7). The species P. expansa (Fig. 1), known as the giant Amazon turtle, is largely distributed throughout the Amazon river and in most of its tributaries (3). The giant Amazon turtle is found in the states of Amapá, Pará, Amazonas, Rondônia, Acre, Roraima, Tocantins, Goiás and Mato Grosso, encompassing equatorial forests and savanna (cerrado) ecosystems in the north and west-central regions of Brazil (3). This reptile can measure from 75 to 107cm in length, 50 to 75cm in width and weigh up to 60kg (9), being the largest fresh water testudine in South America (2, 5, 8). They are long-lived animals with late sexual maturation and a low individual replacement rate (1, 6).